Correction: Highlights from Faraday Discussion 194: Ultrafast Imaging of Photochemical Dynamics, Edinburgh, 2016. Issue 5 (22nd December 2016) - Kirrander, Adam; Minns, Russell S.
Abstract : Correction for 'Highlights from Faraday Discussion 193: Ultrafast Imaging of Photochemical Dynamics, Edinburgh, 2016' by Adam Kirrander and Russell S. Minns, Chem. Commun., 2016, 52, 13631–13636.